Park Forest (L5) and the asteroidal source of shocked L chondrites - Meier, M.; Welten, K.; Riebe, M.; Caffee, M.; Gritsevich, Maria; Maden, C.; Busemann, H. (John Wiley & Sons, Inc., 2017)
© The Meteoritical Society, 2017. The Park Forest (L5) meteorite fell in a suburb of Chicago, Illinois (USA) on March 26, 2003. It is one of the currently 25 meteorites for which photographic documentation of the fireball enabled the reconstruction of the meteoroid orbit. The combination of orbits with pre-atmospheric sizes, cosmic-ray exposure (CRE), and radiogenic gas retention ages (“cosmic histories”) is significant because they can be used to constrain the meteoroid's “birth region,” and test models of meteoroid delivery. Using He, Ne, Ar,10Be, and26Al, as well as a dynamical model, we show that the Park Forest meteoroid had a pre-atmospheric size close to 180 g cm-2, 0–40% porosity, and a pre-atmospheric mass range of ~2–6 tons. It has a CRE age of 14 ± 2 Ma, and (U, Th)-He and K-Ar ages of 430 ± 90 and 490 ± 70 Ma, respectively. Of the meteorites with photographic orbits, Park Forest is the second (after Novato) that was shocked during the L chondrite parent body (LCPB) break-up event approximately 470 Ma ago. The suggested association of this event with the formation of the Gefion family of asteroids has recently been challenged and we suggest the Ino family as a potential alternative source for the shocked L chondrites. The location of the LCPB break-up event close to the 5:2 resonance also allows us to put some constraints on the possible orbital migration paths of the Park Forest meteoroid.